2016
DOI: 10.1021/acs.analchem.6b00854
|View full text |Cite
|
Sign up to set email alerts
|

Multiplexed, Patterned-Paper Immunoassay for Detection of Malaria and Dengue Fever

Abstract: Multiplex assays detect the presence of more than one analyte in a sample. For diagnostic applications, multiplexed tests save healthcare providers time and resources by performing many assays in parallel, minimizing the amount of sample needed and improving the quality of information acquired regarding the health status of a patient. These advantages are of particular importance for those diseases that present with general, overlapping symptoms, which makes presumptive treatments inaccurate and may put the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 25 publications
0
51
0
1
Order By: Relevance
“…Multiplex point-of-care immunoassays for HIV and syphilis as well as mosquito-borne diseases have been tested, and are commercially available for HIV and syphilis. [66][67][68][69] Using bacteriophage display libraries, epitopes for thousands of viral strains have been generated to detect exposure to almost every virus. 58 Diagnosis of neglected tropical diseases such as human African trypanosomiasis and visceral leishmaniasis has traditionally required complex or unreliable serologic methods, but lateral flow tests to replace them have now been developed and commercialized.…”
Section: Traditional Microbiology Techniques Reinvent Themselvesmentioning
confidence: 99%
“…Multiplex point-of-care immunoassays for HIV and syphilis as well as mosquito-borne diseases have been tested, and are commercially available for HIV and syphilis. [66][67][68][69] Using bacteriophage display libraries, epitopes for thousands of viral strains have been generated to detect exposure to almost every virus. 58 Diagnosis of neglected tropical diseases such as human African trypanosomiasis and visceral leishmaniasis has traditionally required complex or unreliable serologic methods, but lateral flow tests to replace them have now been developed and commercialized.…”
Section: Traditional Microbiology Techniques Reinvent Themselvesmentioning
confidence: 99%
“…Proteins play critical roles in regulating biologically relevant activities and therefore are important in biochemistry and physiology . Protein analyses, such as protein fractionation, sequencing, and immunoassays, normally necessitate certain amount of samples being analyzed so as to obtain adequate signals. Unlike cells and DNAs, no valid chemical method exists for protein amplification.…”
Section: Introductionmentioning
confidence: 99%
“…A schematic diagram of the paper-based detection device is shown in Figure 10. Deraney et al [63] reported a patterned paper immunoassay for detection of two malaria antigens, malaria HRP2 and malaria pLDH. They developed a three-dimensional paper-based microfluidic device ( Figure 11) capable of detecting both malaria antigens with high sensitivity which can also distinguish between the two malaria species.…”
Section: Malariamentioning
confidence: 99%